Elastic degradable nasal cavity hemostatic foam dressing and preparation method thereof

A blend of sodium alginate, pectin, gelatin, and carboxymethyl cellulose enhances the mechanical properties and hemostatic performance of nasal packing materials, addressing cost and efficacy issues in existing technologies.

CN119158068APending Publication Date: 2024-12-20BEIJING UNIV OF CHEM TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411297108.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Existing nasal packing materials for sinusitis suffer from high cost, unsatisfactory mechanical properties, and inadequate hemostatic performance, with chitosan foam dressings having insufficient support and elasticity in humid environments and polyurethane-based materials being too expensive.

Method used

A degradable nasal hemostatic foam dressing made from a blend of sodium alginate, pectin, gelatin, carboxymethyl chitosan, and carboxymethyl cellulose, with a two-step cross-linking process and plasticization, enhancing mechanical properties and hemostasis while maintaining biocompatibility and cost-effectiveness.

Benefits of technology

The foam dressing achieves high porosity, water absorption, and improved mechanical properties, providing effective hemostasis with reduced patient discomfort and lower cost compared to existing materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to an elastic degradable nasal cavity hemostatic foam dressing and a preparation method thereof, and solves the technical problems of high material cost and non-ideal mechanical property and hemostatic property in the prior art, the elastic degradable nasal cavity hemostatic foam dressing is prepared from the following components: sodium alginate, pectin, gelatin, carboxymethyl chitosan and carboxymethyl cellulose in a mass ratio of (5.9-6.1): (1.9-2.1): (0.9-1.1): (0.4-0.6): (0.4-0.6); the porosity of the elastic degradable nasal cavity hemostatic foam dressing ranges from 85% to 95%, and the density ranges from 40 mg / cm < 3 > to 50 mg / cm < 3 >. The preparation method can be widely applied to the field of preparation of nasal cavity hemostatic foam dressings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of medical materials, in particular to an elastic and degradable nasal hemostatic foam dressing and a preparation method thereof. Background Art

[0002] Sinusitis is a common upper respiratory tract disease. In China, 10% of the population suffers from or has suffered from sinusitis. According to the duration of the disease, sinusitis is divided into acute sinusitis lasting less than 4 weeks and chronic sinusitis lasting more than 12 weeks. Acute sinusitis is further divided into acute bacterial sinusitis and acute viral sinusitis according to the cause of the disease. Sinusitis can cause patients to produce a large amount of nasal secretions, nasal congestion, facial swelling and pain, and in severe cases, migraines and olfactory decline or even loss. At the same time, sinusitis can cause complications such as orbital cellulitis, subdural empyema, sleep apnea and asthma, so it needs to be treated promptly and effectively. For sinusitis, drug treatment methods can be used, such as isotonic saline nasal irrigation, topical steroids and oral corticosteroids. When drugs cannot effectively treat sinusitis, endoscopic sinus surgery is required. In order to control postoperative bleeding, prevent tissue adhesion and promote wound healing as much as possible, the nasal cavity needs to be packed after endoscopic sinus surgery.

[0003] The first generation of nasal packing materials are mainly inelastic and insoluble materials such as vaseline gauze. This type of material has a low cost, so it is cheap, and the material is relatively smooth, which can meet different packing requirements, but the disadvantages are also very obvious. First of all, it is not breathable, which will cause nasal discomfort and headache. What is more serious is that its surface is rough, the nasal mucosa reacts heavily, and the friction with the nasal cavity is large when it is removed. After removal, the pressure on the nasal blood vessels drops rapidly, which is very likely to cause secondary damage and cause nose bleeding.

[0004] The second generation of nasal packing materials refers to elastic, insoluble materials such as PVA / PVF. This type of material expands by absorbing blood (or injecting saline), has a good effect on nasal compression and hemostasis, is relatively soft, and causes relatively less headache to patients. Studies have shown that this type of packing material is significantly less irritating to the nasal cavity and less adherent to the mucosa than vaseline gauze, but it still causes discomfort to patients.

[0005] The third generation of nasal packing materials refers to bio-based foam dressings, which are characterized by certain elasticity and degradability. Chitosan foam dressings are more common as nasal packing materials. Chitosan materials use biomaterials as raw materials. They have excellent biocompatibility, biodegradability and film-forming ability. In particular, chitosan is the only alkaline polysaccharide with a positive charge in nature. The chitosan hemostatic material made can promote coagulation through electrostatic action. When chitosan dressings come into contact with cell membranes, they promote cell adhesion and aggregation, and promote wound healing. Chitosan foam dressings also have their disadvantages. On the one hand, chitosan's supporting capacity is insufficient, and its elasticity in a humid environment is still very low, and the compression hemostasis effect on the wound is not good. On the other hand, the degradation of chitosan is difficult to control. If it degrades too quickly and breaks quickly, it will not be able to play a good role in nasal packing and hemostasis.

[0006] The fourth generation of nasal packing materials refers to a class of soluble, absorbable, elastic, degradable, high-expansion hemostatic materials such as polyiminoether esters, the most typical of which is the nano-absorbent cotton produced in the Netherlands. The polyurethane bonds of the nano-absorbent cotton provide strong initial compression mechanical properties, while the hydrophilic components are conducive to water absorption and rapid fragmentation. At the same time, its cytotoxicity is very low. No signs of cellular response were observed in the study, and almost no pathological results were observed. Although the performance of nano-absorbent cotton is very good, its high price brings great economic pressure to patients, so it cannot completely replace other types of nasal packing materials. Summary of the invention

[0007] In order to solve the technical problems of high cost, unsatisfactory mechanical properties and hemostatic properties of existing materials, the present invention provides a degradable nasal hemostatic foam dressing with low cost and good mechanical properties and hemostatic properties and a preparation method thereof.

[0008] To this end, the present invention provides an elastic degradable nasal hemostatic foam dressing, which is prepared from the following components in mass ratio: sodium alginate, pectin, gelatin, carboxymethyl chitosan, carboxymethyl cellulose, with a mass ratio of (5.9-6.1): (1.9-2.1): (0.9-1.1): (0.4-0.6): (0.4-0.6); the porosity of the elastic degradable nasal hemostatic foam dressing is 85%-95%, and the density is 40-50 mg / cm 3 The viscosity of the selected sodium alginate is 200-600mPa.s, the selected pectin is 64.5%-100% pure orange peel pectin, and the selected gelatin viscosity is 15mm 2 / s, the selected carboxymethyl chitosan viscosity is 10-80mPa.s, and the selected carboxymethyl cellulose viscosity is 2500-4500mPa.s.

[0009] The present invention also provides a method for preparing an elastic and degradable nasal hemostatic foam dressing, which comprises the following steps: preparing a mixed solution: a: putting gelatin into water, stirring it at room temperature to fully swell it, then heating it, continuing to stir it to completely dissolve the gelatin, and finally adding sodium alginate, pectin, carboxymethyl chitosan and carboxymethyl cellulose and stirring until dissolved to obtain a mixed solution; initial cross-linking: b: adding a primary cross-linking agent to the mixed solution obtained in step a, mixing evenly and then standing to cross-link to obtain a cross-linked solution; c: freeze-drying: the mixed solution obtained in step b The cross-linking solution is pre-frozen, and then dried in a freeze dryer to obtain freeze-dried foam; d: secondary cross-linking: the freeze-dried foam obtained in step c is immersed in a secondary cross-linking agent solution for cross-linking; e: elasticity enhancement: the freeze-dried foam treated in step d is immersed in an elasticity enhancement agent solution for elasticity enhancement, and the soaking elasticity enhancement time is 3 to 6 hours; plasticization: f: the freeze-dried foam treated in step e is immersed in a plasticizer solution for plasticization; g: vacuum drying: the freeze-dried foam treated in step f is dried in a vacuum drying oven to obtain an elastic and degradable nasal hemostatic foam dressing.

[0010] Preferably, the mass volume concentration of the mixed solution in step a is 2.9-3.1% (w / v); the mass ratios of the sodium alginate, pectin, gelatin, carboxymethyl chitosan and carboxymethyl cellulose are (5.9-6.1):(1.9-2.1):(0.9-1.1):(0.4-0.6):(0.4-0.6).

[0011] Preferably, in step b, the primary cross-linking agent is at least one of glutaraldehyde, genipin, and 1,4-butanediol diglycidyl ether; and the amount of the primary cross-linking agent used is 0.09 to 0.11% of the dry weight of the polymer.

[0012] Preferably, in step d, the secondary crosslinking agent is at least one of calcium citrate tetrahydrate, calcium lactate, calcium chloride and calcium sulfate; and the mass volume concentration of the secondary crosslinking agent solution is 2.9-3.1% (w / v).

[0013] Preferably, in step e, the elasticizer is at least one of potassium chloride, potassium dihydrogen phosphate, sodium chloride and disodium hydrogen phosphate; and the concentration of the elasticizer solution is 0.19-0.21 mol / L.

[0014] Preferably, in step f, the plasticizer is at least one of glycerol, ethylene glycol and castor oil; and the mass volume concentration of the plasticizer solution is 5.9-6.1% (w / v).

[0015] The beneficial effects of the present invention are as follows:

[0016] The elastic degradable nasal hemostatic foam dressing of the present invention adopts a blending system of sodium alginate, pectin, gelatin, carboxymethyl chitosan, and carboxymethyl cellulose. Sodium alginate is the main material, and calcium alginate obtained after ion complexation and cross-linking is the main material providing the mechanical properties of the foam dressing. At the same time, the calcium ions released during the degradation process are beneficial to hemostasis; pectin is a controller for the cross-linking of sodium alginate, and the elasticity of the foam dressing is improved by controlling its cross-linking degree; gelatin, carboxymethyl chitosan, and carboxymethyl cellulose provide the gelling properties of the foam dressing and regulate its degradation degree; carboxymethyl chitosan and carboxymethyl cellulose contain a large number of carboxyl groups, which improves the water absorption capacity of the foam dressing. Through such a method of blending multiple materials, the advantages of different materials are combined to obtain a foam dressing with excellent properties.

[0017] The present invention further improves the mechanical properties of the foam dressing by modification methods such as constructing an interpenetrating network structure through two-step cross-linking, making the foam dressing microgel and elasticized by soaking in an ionic solution, and absorbing a non-toxic plasticizer, so that the final product is softer and lighter while maintaining good elasticity, thereby improving the comfort level of patients when using the product.

[0018] The present invention has high porosity and high water absorption performance, and its blood absorption performance is better than that of most common nasal packing materials.

[0019] The various raw materials and auxiliary agents used in the present invention are all non-toxic or low-toxic in nature and the toxicity is removed during the preparation process, so the biocompatibility is good and the safety is high. DETAILED DESCRIPTION

[0020] The present invention is further described below in conjunction with embodiments so that those skilled in the art can easily implement the present invention.

[0021] The content of the present invention is described in detail below through experimental examples, but the scope of the present invention is not limited. The degradation experiment in the characterization experiment of the following examples is to immerse in PBS buffer solution at 37°C for 3 days, and the temperature conditions of other experiments are all 20°C. The mechanical properties are expressed by the compressive strength that produces 40% deformation. All values ​​are the average values ​​of five groups of stable data taken from multiple experiments. The raw materials used in the experimental examples are all conventional commercial products.

[0022] (I) Study on the proportion of main raw materials in the preparation method of foam dressing

[0023] In order to study the effect of the ratio of the main raw materials on the porosity, water absorption capacity, degradability and mechanical properties of the prepared foam dressing, the inventors conducted the following experiments, namely Examples 1 to 5. The experimental results are shown in Table 1.

[0024] Example 1

[0025] A method for preparing an elastic and degradable nasal hemostatic foam dressing comprises the following steps:

[0026] a. Preparation of a mixed solution: gelatin was added to water and stirred at room temperature to fully swell, then the temperature was raised to 50°C and the stirring was continued to completely dissolve the gelatin, and finally sodium alginate, pectin, carboxymethyl chitosan and carboxymethyl cellulose were added and stirred until dissolved to obtain a mixed solution having a concentration of 3% (w / v), and the mass ratio of sodium alginate, pectin, gelatin, carboxymethyl chitosan and carboxymethyl cellulose was 6.1:1.9:1:0.5:0.5;

[0027] b. Primary crosslinking: adding 0.1% (w / w) of glutaraldehyde, genipin, 1,4-butanediol diglycidyl ether and other primary crosslinking agents to the mixed solution obtained in step a, mixing well and standing at 37°C for one day to obtain a crosslinking solution;

[0028] c. Freeze drying: The cross-linking solution obtained in step b was placed at 0°C for 2 hours, then transferred to a -80°C refrigerator for quick freezing for 1 hour, and finally transferred to a -20°C refrigerator for freezing for 5 hours. After freezing, it was dried in a freeze dryer to obtain freeze-dried foam;

[0029] d. Secondary crosslinking: The freeze-dried foam obtained in step c was immersed in a secondary crosslinking agent solution having a concentration of 3% (w / v) prepared with a secondary crosslinking agent such as calcium citrate tetrahydrate, calcium lactate, calcium chloride, calcium sulfate, etc. for 6 hours, and the freeze-dried foam was washed with deionized water after immersion;

[0030] e. Elasticity: The freeze-dried foam treated in step d was soaked in a 0.2 mol / L elasticity agent solution prepared with an elasticity agent such as potassium chloride, potassium dihydrogen phosphate, sodium chloride, disodium hydrogen phosphate, etc. for 6 hours, and the freeze-dried foam was washed with deionized water after soaking;

[0031] f. Plasticization: The freeze-dried foam treated in step e was immersed in a 6% (w / v) solution prepared with a plasticizer such as glycerol, ethylene glycol, castor oil, etc. for 1 h;

[0032] g. Vacuum drying: The freeze-dried foam treated in step f is dried in a vacuum drying oven to obtain a finished foam dressing.

[0033] Example 2

[0034] The content of Example 2 is substantially the same as that of Example 1, except that in step a, the mass ratio of sodium alginate, pectin, gelatin, carboxymethyl chitosan, and carboxymethyl cellulose is 6.1:3:0.9:0.4:0.6.

[0035] Example 3

[0036] The content of Example 3 is substantially the same as that of Example 1, except that in step a, the mass ratio of sodium alginate, pectin, gelatin, carboxymethyl chitosan, and carboxymethyl cellulose is 5.9:2.1:2:0.5:0.5.

[0037] Example 4

[0038] The content of Example 4 is substantially the same as that of Example 1, except that in step a, the mass ratio of sodium alginate, pectin, gelatin, carboxymethyl chitosan, and carboxymethyl cellulose is 6:2:1.1:1.5:0.4.

[0039] Example 5

[0040] The content of Example 5 is substantially the same as that of Example 1, except that in step a, the mass ratio of sodium alginate, pectin, gelatin, carboxymethyl chitosan, and carboxymethyl cellulose is 5.9:2:1:0.6:1.5.

[0041] Table 1 Effect of the proportion of main raw materials on the properties of the prepared foam dressing

[0042]

[0043]

[0044] As shown in Table 1, sodium alginate, as the main material of foam dressings, contributes greatly to the porosity and mechanical properties. The addition of pectin can improve the mechanical properties of foam dressings by controlling the degree of cross-linking and further improve its elasticity. Gelatin, carboxymethyl chitosan and carboxymethyl cellulose will gel in a wet environment, regulating the degree of degradation of the foam dressing. Carboxymethyl chitosan and carboxymethyl cellulose have a large number of carboxyl groups, which can improve the water absorption capacity of foam dressings.

[0045] (II) Study on the concentration of mixed solution in the preparation method of foam dressing:

[0046] In order to study the effect of the concentration of the mixed solution on the porosity, water absorption capacity and mechanical properties of the prepared foam dressing, the inventors conducted the following experiments, namely, Example 1, Example 6, Example 7, Example 8 and Example 9. The experimental results are shown in Table 2.

[0047] Embodiment 6:

[0048] The content of Example 6 is substantially the same as that of Example 1, except that the concentration of the mixed solution in step a is 1% (w / v).

[0049] Embodiment 7:

[0050] The content of Example 7 is substantially the same as that of Example 1, except that the concentration of the mixed solution in step a is 2% (w / v).

[0051] Embodiment 8:

[0052] The content of Example 8 is substantially the same as that of Example 1, except that the concentration of the mixed solution in step a is 4% (w / v).

[0053] Embodiment 9:

[0054] The content of Example 9 is substantially the same as that of Example 1, except that the concentration of the mixed solution in step a is 5% (w / v).

[0055] Table 2 Effect of mixed solution concentration on the properties of foam dressings

[0056]

[0057] As shown in Table 2, as the concentration of the mixed solution increases, the porosity and water absorption of the foam dressing gradually decrease, and the mechanical properties gradually improve. By comparing with some nasal packing materials on the market, it is believed that when the concentration of the mixed solution is 3% (w / v), the prepared foam dressing has both excellent water absorption and moderate mechanical properties.

[0058] (III) Study on the concentration of elasticizing agent and soaking time in the preparation method of foam dressing

[0059] In order to study the effects of the concentration of the elasticizing agent and the soaking elasticizing time on the water absorption capacity and mechanical properties of the foam dressing, the inventors conducted the following experiments, namely, Example 1, Example 10, Example 11, Example 12, Example 13, Example 14, Example 15, Example 16, and Example 17. The experimental results are shown in Table 3.

[0060] The content of Example 10 is basically the same as that of Example 1, except that step e is skipped.

[0061] The contents of Example 11 are substantially the same as those of Example 1, except that the concentration of the elasticizing agent solution in step e is 0.1 mol / L.

[0062] The content of Example 12 is basically the same as that of Example 1, except that the concentration of the elasticizer solution in step e is 0.3 mol / L.

[0063] The content of Example 13 is substantially the same as that of Example 1, except that the concentration of the elasticizer solution in step e is 0.4 mol / L.

[0064] The contents of Example 14 are substantially the same as those of Example 1, except that the concentration of the elasticizing agent solution in step e is 0.5 mol / L.

[0065] The content of Example 15 is substantially the same as that of Example 1, except that the soaking time of the elasticizing agent solution in step e is 3 hours.

[0066] The content of Example 16 is substantially the same as that of Example 1, except that the soaking time of the elasticizing agent solution in step e is 12 hours.

[0067] The content of Example 17 is substantially the same as that of Example 1, except that the soaking time of the elasticizing agent solution in step e is 24 hours.

[0068] Table 3 Effects of elasticizing agent concentration and immersion elasticizing time on the properties of foam dressings

[0069]

[0070] As can be seen from Table 3, the elasticizing step is actually a process of increasing water absorption and reducing mechanical properties. As the concentration of the elasticizing agent solution increases, the water absorption of the foam dressing continues to increase, and the compression strength continues to decrease. In fact, when the compression strength is lower than 100 kPa, the foam dressing loses most of its elasticity. Similarly, as the soaking time of the elasticizing agent solution increases, the water absorption of the foam dressing continues to increase, and the compression strength continues to decrease. However, after the soaking time reaches 6 hours, the data hardly change. The reason is that the elasticizing mechanism of the elasticizing agent in the present invention is to partially de-crosslink the foam dressing through ion exchange, and this process basically reaches equilibrium after 6 hours.

[0071] The above description is only for the preferred embodiments of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the scope of the claims of the present invention shall be within the scope of protection of the present invention.

Claims

1. An elastic and degradable nasal hemostatic foam dressing, characterized in that: The invention is prepared from the following components in the following mass ratios: sodium alginate, pectin, gelatin, carboxymethyl chitosan, and carboxymethyl cellulose, with the mass ratio being (5.9-6.1):(1.9-2.1):(0.9-1.1):(0.4-0.6):(0.4-0.6); the elastic degradable nasal hemostatic foam dressing has a porosity of 85%-95% and a density of 40-50 mg / cm 3 .

2. The method for preparing the elastic degradable nasal hemostatic foam dressing according to claim 1, characterized in that: The following steps are involved: a. Preparation of a mixed solution: Add gelatin into water, stir at room temperature to fully swell it, then heat it up, continue stirring to completely dissolve the gelatin, and finally add sodium alginate, pectin, carboxymethyl chitosan and carboxymethyl cellulose and stir until dissolved to obtain a mixed solution; b. Primary crosslinking: adding a primary crosslinking agent to the mixed solution obtained in step a, mixing evenly and standing to crosslink to obtain a crosslinked solution; c. Freeze drying: pre-freezing the cross-linking solution obtained in step b, and then drying it in a freeze dryer to obtain a freeze-dried foam; d. Secondary crosslinking: the freeze-dried foam obtained in step c is immersed in a secondary crosslinking agent solution for crosslinking; e. Elasticity: soak the freeze-dried foam after step d in an elasticity enhancing agent solution for elasticity enhancement, the soaking time for elasticity enhancement is 5.5 to 6.5 hours; f. Plasticizing: soaking the freeze-dried foam after the treatment in step e in a plasticizer solution for plasticization; g. Vacuum drying: The freeze-dried foam treated in step f is dried in a vacuum drying oven to obtain an elastic and degradable nasal hemostatic foam dressing.

3. The method for preparing the elastic degradable nasal hemostatic foam dressing according to claim 2, characterized in that: The mass volume concentration of the mixed solution in step a is 2.9-3.1%; the mass ratios of the sodium alginate, pectin, gelatin, carboxymethyl chitosan and carboxymethyl cellulose are (5.9-6.1):(1.9-2.1):(0.9-1.1):(0.4-0.6):(0.4-0.6).

4. The method for preparing the elastic degradable nasal hemostatic foam dressing according to claim 2, characterized in that: In the step b, the primary cross-linking agent is at least one of glutaraldehyde, genipin, and 1,4-butanediol diglycidyl ether; the amount of the primary cross-linking agent is 0.09-0.11% of the dry weight of the polymer.

5. The method for preparing the elastic degradable nasal hemostatic foam dressing according to claim 2, characterized in that: In the step d, the secondary cross-linking agent is at least one of calcium citrate tetrahydrate, calcium lactate, calcium chloride and calcium sulfate; and the mass volume concentration of the secondary cross-linking agent solution is 2.9-3.1%.

6. The method for preparing the elastic degradable nasal hemostatic foam dressing according to claim 2, characterized in that: In the step e, the elasticizer is at least one of potassium chloride, potassium dihydrogen phosphate, sodium chloride, and disodium hydrogen phosphate; and the concentration of the elasticizer solution is 0.19-0.21 mol / L.

7. The method for preparing the elastic degradable nasal hemostatic foam dressing according to claim 2, characterized in that: In the step f, the plasticizer is at least one of glycerol, ethylene glycol and castor oil; and the mass volume concentration of the plasticizer solution is 5.9-6.1%.